Climate variability and mining sustainability: exploring operations' perspectives on local effects and the willingness to adapt in Ghana - Salamatu J. Tannor; Christian Borgemeister; Shalom D. Addo–Danso; Klaus Greve; Bernhard Tischbein (SN Business & Economics, 2023)
The mining industry is susceptible to the effects of local climatic changes just as the surrounding socioecological systems are exposed to both mining and changing climate impacts. Adaptation deficit in mining is a worldwide problem but given the double exposure of surrounding systems, which has emergent outcomes on the industry, operations must adapt to coexist with surrounding rural communities. To understand this susceptibility, the study employed mixed methods to assess the implications of local climatic changes on mining sustainability as perceived among Ghanaian operations through the lens of the corporate adaptation process framework. The results indicate that operational workers are aware of increasing variability in the climatic patterns across southwestern Ghana, citing changes in the start/end of the rain season, torrential rain, prolonged dry season, and a general increase in temperature. The effects of these changing patterns, which affect mining activities, are diverse, including mine water management, safety, and occupational health issues as well as production planning opportunities. Workers ranked high the need to involve stakeholders such as the state-appointed regulators and Ghana Chamber of Mines as key strategies to enjoin adaptation to changing climate at operational sites. In addition, workers perceived the impact on regulatory and economic sustainability performances as major factors determining the industry's perception and willingness to adapt. The study highlights pertinent issues useful for informed policy decision-making in the strive towards attaining sustainable development goals, especially Goal 13, which calls for active collaboration between business and society.
Keywords: 330; Climate adaptation; Corporate sustainability; Double exposure; Extractives